Effects of Foliar Selenite on the Nutrient Components of Turnip (Brassica rapa var. rapa Linn.) - Li, Xiong; Li, Boqun; Yang, Yongping (Frontiers in Chemistry, 2018)
We administered foliar applications of 50, 100 and 200 mg L−1 selenium (Se, selenite) on turnip (Brassica rapa var. rapa Linn.) and detected the changes in the main nutrient components in fleshy roots. Results showed that the foliar application of Se (Ⅳ) significantly increased the Se content in turnip, and Se (Ⅳ) positively affected the uptake of several mineral elements, including magnesium, phosphorus, iron, zinc, manganese and copper. Se (Ⅳ) treatments also improved the synthesis of protein and multiple amino acids instead of crude fat and total carbohydrate in turnip, indicating that the foliar application of Se (Ⅳ) could enhance Se biofortification in turnip and promote its nutritional value. We recommended 50–100 mg L−1 Se treatment for foliar application on turnip based on the daily intake of Se for adults (96–139 µg person−1 day−1) and its favourable effects on the nutrient components of turnip.